Determination of residual tin in synthesized aliphatic biomedical polyesters by electrothermal atomic absorption spectroscopy - Sobczak, M.; Żółtowska, K.; Jaklewicz, A.; Kołodziejski, W. (Polimery, 2010)
The synthesis of the aliphatic polyesters - polylactide (PLA) and poly (e-caprolactanes) (PCL) in the ring-opening polymerization of cyclic esters in the presence tin(II) 2-ethylhexanoate (SnOct2) has been presented. The obtained products were subjected to multiple purification procedures to remove residual organotin catalyst (Tables 2 and 3). The tin content in the polyesters was then determined by Electrothermal Atomic Absorption Spectroscopy (ET-AAS) (Tables 3 and 4) after each purification process. The results of the analysis were discussed taking into consideration the requirements placed by the European Pharmacopoeia regarding the amount of tin allowed in aliphatic biomedical polyesters. It was confirmed, that a four-stage purification of the polyreaction product led to a three-fold decrease in the concentration of tin to a level less than the value required by Pharmacopoeia for materials designated for contact with blood. Moreover, the purification process did not generate any degradation of the polymer.